The presence of depression in de novo Parkinson's disease reflects poor motor compensation. - Yoonju Lee (PLoS ONE, 2018)
Depression frequently accompanies Parkinson's disease and often precedes the onset of motor symptoms. This study aimed to evaluate the impact of depression on motor compensation in patients with de novo Parkinson's disease. This retrospective cohort study analyzed data from 474 non-demented patients with de novo Parkinson's disease (mean age, 64.6±9.8 years; 242 men) who underwent both dopamine transporter PET scan and depression assessment using the Beck Depression Inventory at baseline. Patients were classified into tertiles by Beck Depression Inventory score. At baseline, high-tertile group (Beck Depression Inventory score ≥15, n = 157) showed more severe motor deficits and lower cognitive function than low-tertile group (Beck Depression Inventory score ≤7, n = 158, P = 0.034 and P = 0.008, respectively). Greater motor deficits in high-tertile group than low-tertile group remained significant after controlling for dopamine transporter binding in the posterior putamen, as well as other confounding variables. During follow-up of a median duration of 47 months, high-tertile group received higher levodopa-equivalent doses for symptom control than did low-tertile group after controlling for age, gender, and initial motor deficit severity. These results demonstrate that depression in de novo Parkinson's disease is associated with motor deficit severity at baseline and dose of PD medications during follow-up, suggesting that the presence of depression in de novo Parkinson's disease represents poor motor compensation.